Erdheim-Chester disease presenting with eruptive fibrous histiocytomas - Michael J. Martinez; Shane A. Meehan; Ian W. Tattersall (Wiley, 2024)
Abstract Erdheim-Chester disease (ECD) is a rare, non‐Langerhans histiocytic disease, with the manifestation of cutaneous lesions becoming further recognised and understood. Most commonly presenting with xanthelasma‐like lesions, cutaneous manifestations are the first noticeable sign of ECD in a significant number of patients. Other commonly reported cutaneous lesions of ECD include panniculitis‐like lesions and granuloma annulare‐like lesions. While previously reported papular lesions of ECD include crusty yellow and erythematous papules, small, pink to fleshy coloured papules, and verruca plana‐like papules, papulonodular eruptions consistent with fibrous histiocytomas are a rare and underreported sequala of ECD. Here, we report an 86‐year‐old male with a history of prostate and bladder cancer who presented with eruptive fibrous histiocytomas, prompting workup that lead to a diagnosis of ECD. The patient received expedited imaging given the rare association of eruptive fibrohistiocytic lesions with malignancy, revealing diffuse perinephric and urothelial soft tissue thickening and enhancement, which was biopsied and found to harbour the BRAF V600E mutation. One could reasonably hypothesise that the pathologic mechanism occurring in the perinephric and urothelial soft tissue areas of this patient bodes similarities to the cutaneous sites consistent with the fibrohistiocytic lesions. This may present a potential clue to the poorly understood origin and pathogenesis of ECD.